SYNERGY OF ISLAMIC BOARDING SCHOOL MANAGEMENT AND SHARIA ECONOMICS IN FOSTERING THE INDEPENDENCE OF AT-TAMUR STUDENTS - Intan Nurrachmi; Panji Adam Agus Putra (CV. RADJA PUBLIKA, 2025)
Pesantren in this day and age must be an educational institution that instills Islamic values as a whole, both teaching worship procedures and social social procedures. The management of the pesantren must synergize with other fields in order to make students independent in meeting their life needs. This study aims to analyze the synergy between pesantren management and sharia economics in fostering student independence at the At-Tamur Islamic Boarding School. The research method used is qualitative with a case study approach. Data were collected through observations, in-depth interviews, and documentation studies. The results of the study show that the integration between effective pesantren management and the application of sharia economic principles is able to create an environment that supports the development of student independence. Programs such as sharia cooperatives, entrepreneurship training, and sharia-based financial management are the main keys in achieving these goals. This synergy not only increases the financial independence of students but also forms a character in accordance with Islamic values.